2021
DOI: 10.1002/met.2027
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of potential evapotranspiration values based on vine copula

Abstract: Vine copula had a great impact on the study and analysis of dependence structures in various sciences. In multivariate analyses with dimensions of more than two variables, it is associated with computational complexities that solve vine copulas and these problems. In this study, in order to provide an approach to simulate potential evapotranspiration based on meteorological parameters in Birjand meteorological station from different family copulas including Rvine, independent R-vine, Gaussian, independent Gaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Various studies in the field of simulation and modeling of different meteorological and hydrological parameters show that the copula function has recently been considered by various researchers. Copula-based simulation has best acceptable certainty due to the involvement of proportional data distribution in modeling and simulation as well as the use of conditional density of copula functions (De Michele and Salvadori, 2003;De Michele et al 2005;Salvadori and De Michele, 2004, 2007, and 2010Salvadori et al, 2007 andTahroudi et al, 2020a&b;Khashei-Siuki et al 2021). Copula functions increase the accuracy of simulations and improve their certainly by considering the marginal distribution of data in simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies in the field of simulation and modeling of different meteorological and hydrological parameters show that the copula function has recently been considered by various researchers. Copula-based simulation has best acceptable certainty due to the involvement of proportional data distribution in modeling and simulation as well as the use of conditional density of copula functions (De Michele and Salvadori, 2003;De Michele et al 2005;Salvadori and De Michele, 2004, 2007, and 2010Salvadori et al, 2007 andTahroudi et al, 2020a&b;Khashei-Siuki et al 2021). Copula functions increase the accuracy of simulations and improve their certainly by considering the marginal distribution of data in simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Vine copulas with a wide variety of tree sequences allow the selection of different structures that improve the results. Khashei-Siuki et al (2021) to simulation of potential evapotranspiration at Birjand meteorological station, Iran used vine copulas. The results of the simulation of the potential evapotranspiration given by precipitation, air temperature and relative humidity using vine copulas showed a NSE= 92%.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) and Khashei‐Siuki et al . (2021) used vine copula to simulate flood hydrograph and potential evapotranspiration model, respectively, in their studies. They found that the efficiency of vine copula in dependence analysis was good and accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The complete freedom to select bivariate copula in each step of hierarchical structure provides elevated flexibility in vine copula based multivariate dependence modelling than traditional copulas (Ni et al, 2020). Based on this aspect, Tahroudi et al (2021) and Khashei-Siuki et al (2021) used vine copula to simulate flood hydrograph and potential evapotranspiration model, respectively, in their studies. They found that the efficiency of vine copula in dependence analysis was good and accurate.…”
Section: Introductionmentioning
confidence: 99%